2021
DOI: 10.3390/ma14102679
|View full text |Cite
|
Sign up to set email alerts
|

RE-Based Inorganic-Crystal Nanofibers Produced by Electrospinning for Photonic Applications

Abstract: Electrospinning is an effective and inexpensive technique to grow polymer materials in nanofiber shape with exceptionally high surface-area-to-volume ratio. Although it has been known for about a century, it has gained much interest in the new millennium thanks to its low cost and versatility, which has permitted to obtain a large variety of multifunctional compositions with a rich collection of new possible applications. Rare-earth doped materials possess many remarkable features that have been exploited, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 114 publications
(297 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have proved that inner ear stem cells have multidifferentiation potential and can differentiate into hair cells under certain induction conditions [16]. In addition, the scaffolds prepared by the electrospinning have a micro/nano structure and a large surface area-to-volume ratio [47]. At the same time, the scaffolds also can mimic the structure of the natural ECM, which can enhance cell attachment, proliferation and differentiation [48].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved that inner ear stem cells have multidifferentiation potential and can differentiate into hair cells under certain induction conditions [16]. In addition, the scaffolds prepared by the electrospinning have a micro/nano structure and a large surface area-to-volume ratio [47]. At the same time, the scaffolds also can mimic the structure of the natural ECM, which can enhance cell attachment, proliferation and differentiation [48].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the collector temperature and atmosphere humidity can have a large influence on the fiber quality. The electrospinning technique naturally leads to the growth of amorphous materials; therefore, a calcination step is always needed to obtain crystal nanofibers [ 86 ]. Among the obstacles and difficulties is the complexity of the fabrication process, the range of materials that can be spun, the homogeneity of the fibers, and reproducibility.…”
Section: Challenges In Embedding Ucnp’s In Nanofibermentioning
confidence: 99%
“…Additionally, research by Stachewicz et al [28] demonstrated the impregnation of nylon (PA6) nanofibers into a high-concentration polymer solution, which, while improving the mechanical properties of the PA6 nanofiber mat, compromised its porosity, because the PVA solution filled the gaps within the mat, transforming it into a composite polymeric film. Meanwhile, Tang et al [29] have illustrated that a dip-coating method is predominantly utilized to fabricate functional fibrous materials for applications such as self-cleaning surfaces [30], conductive textiles [31], oil-water separation [32], energy storage [33], and photonic crystals [34].…”
Section: Introductionmentioning
confidence: 99%